Palabas at Paloob: Tambalang Mukha ng Pagtula - Almario, Virgilio S. (Philippine Humanities Review, 2016)
National Artist for Literature Virgilio S. Almario explains the literary concepts “palabas” and “paloob” first introduced in the 1980s as distinct characteristics of two leading poetic traditions in the country: Balagtasism and Modernism. Almario cites several examples across generations of poets and poetry in order to clarify the intertwined relation between the two. Keywords: palabas, paloob, literary traditions, Balagtasism, Modernism